Al-Qur’an dan Pengentasan Kemiskinan; Studi Pemahaman Zakat dan Problematikanya pada Masyarakat Desa Tembok Luwung Kec. Adiwerna Kab. Tegal - Aulia Rakhman, Itmam (Prodi Ilmu al-Qur'an dan Tafsir, 2020)
Poverty and social inequality are serious problems and need serious handling as well. Al-Qur'an in several verses also talks about poverty alleviation, both in the phase of Mecca and Medina. One of the instruments that the Qur'an calls for is zakat, which actually has a big potential if it is managed optimally. However, the understanding of the Muslim community regarding zakat is not fully complete, in addition to the lack of literacy in this matter, socialization related to zakat and its benefits has not been carried out massively in society, both at the formal and non-formal levels of education. This research was conducted in Tembok Luwung Village, Kec. Adiwerna Kab. Tegal during the month of Ramadan in 1439 H / 2018 M. in several places of worship (prayer rooms, mosques, and majlis Ta'lim) which held a recitation activity